2006
DOI: 10.1007/s10067-006-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vasculitides in Turkey: a nationwide survey

Abstract: This is the largest multicenter study defining the demographic data for childhood vasculitides. The distribution of childhood vasculitides was different in our population where KD is much less frequent, whereas HSP constitutes an overwhelming majority. C-PAN was more frequent as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 14 publications
2
35
0
5
Order By: Relevance
“…Like our study, Gülhan et al (2) were noticed that there was no gender predominance in Turkish children with KD, and they also mentioned that the earlier occurrence of desquamation and cardiovascular disease than expected by conventional teaching. Likewise previous Turkish patient series (1)(2)(3)(4), the most common clinical finding was changes in the lips and oral cavity in our study. We also observed that most of our patients were irritable at the time of the diagnosis.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Like our study, Gülhan et al (2) were noticed that there was no gender predominance in Turkish children with KD, and they also mentioned that the earlier occurrence of desquamation and cardiovascular disease than expected by conventional teaching. Likewise previous Turkish patient series (1)(2)(3)(4), the most common clinical finding was changes in the lips and oral cavity in our study. We also observed that most of our patients were irritable at the time of the diagnosis.…”
supporting
confidence: 84%
“…Kawasaki disease (KD) has replaced acute rheumatic fever as the most common cause of acquired heart disease in children in developed countries and occurs in 9% of childhood vasculitis in our country (1). There are few studies concerning the characteristic features of Turkish children diagnosed with KD (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue has been reported as the most common presentation of TA in children, and other signs and symptoms are hypertension (83%), headache (31%), weight loss (22%), arthritis/arthralgia (14%) and fever (2%) (1)(2)(3)(4)(5). Both of our patients had fatigue, hypertension, weight loss and headache.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated, the next phase affects the aorta and its main branches so that affected vessels may become stenotic and aneurysms may develop (2,3). Presenting symptoms at the second stage usually reflect end-organ ischemia with cold extremities, poor or absent of arterial pulses and claudication (2).…”
Section: Introductionmentioning
confidence: 99%